Hepatoprotective Activity, In Silico Analysis, and Molecular Docking Study of Verbascoside from Leucophyllum frutescens in Rats with Post-Necrotic Liver Damage - Osmar Antonio Jaramillo-Morales; Erik Díaz-Cervantes; Lisa Dalla Via; Aida Nelly Garcia-Argaez; Josué Vidal Espinosa-Juárez; José Carlos Ovando-Zambrano; Victor Manuel Muñoz-Pérez; Carmen Valadez-Vega; Mirandeli Bautista (MDPI AG, 2023)
There is an urgent need for scientists to verify the pharmacological properties of medicinal plants. Leucophyllum frutescens (Lf) belongs to the family Scrophulariaceae, and it is used in the treatment of airway diseases such as cough, tuberculosis, and asthma. The methanolic extract of the aerial parts of Lf allows for the isolation and identification of verbascoside (Vb). This study aimed to evaluate the hepatoprotective effect of Vb, a caffeoyl phenylethanoid glycoside (CPG), on post-necrotic liver damage induced by thioacetamide (TA) via in vivo and in silico studies, with the latter considering a cancerous process. The aerial parts of Lf were extracted by maceration using hexane methanol (5 L/500 g/8 days). Vb was isolated from methanol extract at approximately 30%. Wistar rats were intragastrically pretreated or not with a single dose of Vb (20 mg/kg) for four days. On the fourth day, a single dose of TA (6.6 mmol/kg) was intraperitoneally injected. Blood samples and parameters related to liver damage, like AST and ALT, were obtained. Vb significantly reduced the level of liver injury following thioacetamide-induced necrosis. This was corroborated by in silico assay and docking studies, demonstrating that Vb can interact with a HeLa target through hydrogen bonds and electrostatic interactions, achieving better performance than commercial chemotherapeutic Taxol®, by 0.34 kcal/mol. AST and ALT were significantly lower in the rats pretreated with Vb. Furthermore, Vb did not induce cytotoxicity and had a median lethal dose (LD50) greater than 5000 mg/kg. These results suggest that Vb may be used as an alternative to reduce liver damage.